2011
DOI: 10.17305/bjbms.2011.2598
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral retinal detachment in a case of preeclampsia

Abstract: Serous retinal detachment is an unusual cause of visual loss in preeclampsia. We report the case of 24-years-old primipara with severe preeclampsia who developed bilateral serous retinal detachment a few hours after delivery. A few weeks after delivery there was spontaneous resorption of the subretinal fluid and complete resolution bilateral serous retinal detachment, with residual pigmentary changes of the retinal pigment epithelium. Visual acuity was normal in each eye. The management of retinal detachment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 11 publications
2
24
0
Order By: Relevance
“…[19] Other causes of blindness in preeclampsia are exudative retinal detachment and hypertensive retinopathy. [20] The neonatal complications associated with preeclampsia include intrauterine growth retardation, Intrauterine deaths, complications associated with preterm deliveries, intracranial haemorrhage, respiratory distress, surfactant deficiency induced hyaline membrane disease, neonatal sepsis, bronchopulmonary dysplasia and need for NICU admissions. [21] As the only definitive management of severe eclampsia is delivery it becomes of utmost importance to keep in mind the effect such a preterm delivery might have on newborn.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Other causes of blindness in preeclampsia are exudative retinal detachment and hypertensive retinopathy. [20] The neonatal complications associated with preeclampsia include intrauterine growth retardation, Intrauterine deaths, complications associated with preterm deliveries, intracranial haemorrhage, respiratory distress, surfactant deficiency induced hyaline membrane disease, neonatal sepsis, bronchopulmonary dysplasia and need for NICU admissions. [21] As the only definitive management of severe eclampsia is delivery it becomes of utmost importance to keep in mind the effect such a preterm delivery might have on newborn.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Bilateral retinal detachments have also been reported in association with serum sickness, 9 cytomegalovirus retinitis, 10 carotidcavernous fistula, 11 Marfan syndrome, 12 and nonaccidental pediatric injury 13 . In this case, the finding of bilateral retinal detachments, in combination with an elevated blood pressure, is what prompted us to consider the diagnosis of preeclampsia in a patient who did not know that she was pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if there is excessive necrosis in the retinal pigment epithelium, permanent loss of vision may occur. [23] Lee et al reported that ocular symptoms and visual sequelas usually become reversed with the immediate termination of the pregnancy. [24] In our study, we observed that the retinal detachments of the patients, who were followed up after labor, recovered without the need of surgical procedure.…”
Section: Discussionmentioning
confidence: 99%